2013
DOI: 10.1590/s0100-736x2013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Perfil da infecção pelo vírus da diarreia viral bovina (BVDV) em um rebanho bovino leiteiro de alta produção e com programa de vacinação contra o BVDV

Abstract: A infecção pelo vírus da diarreia viral bovina (BVDV) foi avaliada em um rebanho bovino leiteiro de alta produção com histórico de problemas reprodutivos e de vacinação regular contra o BVDV. A identificação do vírus foi realizada por RT-PCR em soro sanguíneo e o perfil sorológico por vírus-neutralização. Inicialmente, 100% (n=692) dos animais do rebanho foram avaliados com relação à presença de infecção ativa pelo BVDV por meio da RT-PCR. Quatro meses após, todos os animais positivos (n=29) na primeira avalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
1
7
0
5
Order By: Relevance
“…PI animals exhibit immunotolerance to the homologous strain of the virus, but may be immunocompetent relative to other strains, unlike induced tolerance. In these cases, the PI animal may be positive for the virus (direct testing of the agent by PCR or ELISA antigen) and the reagent in the seroneutralization test for the heterologous strain (antibodies) (DEZEN et al, 2013). Further studies should be conducted in this region to identify PI animals and to determine the percentage of these animals in herds, given that they act as potential sources of infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PI animals exhibit immunotolerance to the homologous strain of the virus, but may be immunocompetent relative to other strains, unlike induced tolerance. In these cases, the PI animal may be positive for the virus (direct testing of the agent by PCR or ELISA antigen) and the reagent in the seroneutralization test for the heterologous strain (antibodies) (DEZEN et al, 2013). Further studies should be conducted in this region to identify PI animals and to determine the percentage of these animals in herds, given that they act as potential sources of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Sanitary measures, based on risk factors are the basis for effective sanitary management (NISKANEN; LINDBERG, 2003). The adoption of specific measures, such as the disinfection of veterinary instruments (FODDAI et al, 2014), vaccination (RIBEIRO;PEREIRA, 2004;DEZEN et al, 2013), the identification and elimination of PI animals (RIBEIRO; PEREIRA, 2004) and laboratory examinations for replacement animals (SMITH et al, 2014) are indicated as effective measures to control BVDV infection. Coupled with increased knowledge of the disease, the adoption of such measures could lead to improved production efficiency and increased economic profitability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neste sentido, um programa de vacinação, por exemplo, não previne todas as infecções em animais individualmente . Dezen et al (2013) …”
Section: Discussionunclassified
“…In Brazil, the main causes of congenital malformations in ruminants are the ingestion of toxic plants, such as Mimosa tenuiflora (PIMENTEL et al, 2007;DANTAS et al, 2010) and Poincianella pyramidalis (REIS et al, 2016;MARCELINO et al, 2017), restricted to the Caatinga Biome, in the semiarid region of Northeast Brazil, and absent from the property in the present report. Other infectious agents of congenital malformations and reproductive alterations, such as embryonic death and abortion, included the BVDV (PAVARINI et al, 2008;DEZEN et al, 2013) and bluetongue virus (LAGER, 2004;ANTONIASSI et al, 2010). In the dairy basin from which this calf originated, a molecular diagnosis of BVDV infection had been performed in a cow that aborted a 4-monthold fetus (LOPES et al, 2016).…”
Section: Introductionmentioning
confidence: 99%